Interaction of nitric oxide and salivary gland epidermal growth factor in the modulation of rat gastric mucosal integrity. - Tepperman, B. L. (Nature Publishing Group, 1993)
1. The interaction between endogenous nitric oxide (NO) and factors from the rat submandibular salivary gland such as epidermal growth factor (EGF) on gastric mucosal integrity in the rat has been investigated. 2. Bolus administration of the NO synthase inhibitor, NG nitro-L-arginine methyl ester (L-NAME; 6.25-50 mg kg-1, i.v.) to animals treated intraluminally with 0.15 N HCl resulted in a significant increase in the area of mucosal haemorrhagic damage at doses 12.5 and 50 mg kg-1. Concurrent administration of indomethacin (5 mg kg-1, i.v.) resulted in a significant haemorrhagic mucosal damage in response to L-NAME (12.5-50 mg kg-1). Administration of the highest dose of L-NAME resulted in an increase in histological damage to the rat gastric mucosa. 3. When compared to control animals, the extent of damage produced by L-NAME or L-NAME in combination with indomethacin was significantly exacerbated in rats which had been sialoadenectomized (SALX) by removal of the submandibular salivary glands. The mucosal damage in SALX rats was ameliorated by treatment with EGF (5 and 10 micrograms kg-1, i.v.). 4. L-NAME administration resulted in a small reduction of gastric mucosal blood flow as assessed by laser Doppler flowmetry (LDF). The reduction in LDF by 25 and 50 mg kg-1 L-NAME was significantly greater in SALX rats than in rats with intact salivary glands. Pretreatment of SALX rats with indomethacin did not augment this large decrease in LDF suggesting that endogenous prostanoids do not interact with NO and salivary factors in regulating mucosal microcirculation.(ABSTRACT TRUNCATED AT 250 WORDS)